CSR, Social Media, Perceived Value, and Customer Loyalty in Fast-Food SMEs - Marzuki, Marzuki; Imaningsih, Erna Sofriana (International Journal Labs, 2026)
The fast-food SME partnership sector faces increasingly intense competition alongside rapid digital transformation. Business partners demand transparent communication, consistent operational support, and strong brand value to sustain profitability and long-term collaboration. Sukaku Fried Chicken experienced fluctuations in partner turnover, indicating that Corporate Social Responsibility (CSR), social media marketing, and perceived value may not yet be optimally translated into satisfaction and loyalty. Strengthening strategic alignment among these variables is therefore essential to maintain sustainable partner relationships. This study aims to analyze the influence of Corporate Social Responsibility (CSR), social media marketing, and perceived value on customer loyalty, with customer satisfaction as a mediating variable in the SME fast-food partnership context. This research employed a quantitative survey design involving 163 Sukaku Fried Chicken business partners selected through purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine both direct and indirect relationships among variables. The findings reveal that CSR directly influences customer loyalty but does not significantly affect customer satisfaction. Social media marketing and perceived value significantly influence customer satisfaction, and customer satisfaction significantly influences loyalty. Furthermore, customer satisfaction fully mediates the effects of social media marketing and perceived value on loyalty, but does not mediate the relationship between CSR and loyalty. Customer satisfaction plays a central mediating role in building loyalty within SME partnerships. Managerially, the company should prioritize satisfaction-driven strategies by strengthening interactive digital engagement, enhancing perceived partner benefits, and aligning CSR initiatives with tangible partner impacts to ensure sustainable business loyalty.